Manipulation in the Enrollment of Research Participants - Mandava, Amulya (The Hastings Center report, 2013)
Recruitment is a challenge for many biomedical research studies with human participants. Strategies to increase the speed and ease of recruitment are therefore valuable. One way to improve these strategies is to design them so as to make use of other factors that play a role in potential participants’ decisions. In this paper, we analyze the noncoercive ways in which researchers can use knowledge about the decision-making tendencies of potential participants in order to motivate them to consent to research enrollment. We identify which modes of influence preserve respect for participants’ autonomy and which disrespect autonomy, applying the umbrella term “manipulation” to the latter. We then apply our analysis to a series of cases adapted from the experiences of clinical researchers in order to develop a framework for thinking through the ethics of manipulating people into research participation. All manipulation disrespects autonomy and is therefore pro tanto wrong. However, only deceptive manipulation invalidates the consent that results from it. Use of the other forms of manipulation can be permissible, but only if the outcome of using manipulation is sufficiently good, and the research cannot be carried out using ethically preferable means to obtain consent.